Prognostic factors for return to work after depression-related work disability: A systematic review and meta-analysis - Ervasti, Jenni; Joensuu, Matti; Pentti, Jaana; Oksanen, Tuula; Ahola, Kirsi; Vahtera, Jussi; Kivimäki, Mika; Virtanen, Marianna (Journal of psychiatric research, 2017)
Knowledge about factors influencing return to work (RTW) after depression-related absence is highly relevant, but the evidence is scattered. We performed a systematic search of PubMed and Embase databases up to February 1, 2016 to retrieve cohort studies on the association between various predictive factors and return to work among employees with depression for review and meta-analysis. We also analyzed unpublished data from the Finnish Public Sector study. Most-adjusted estimates were pooled using fixed effects meta-analysis. Eleven published studies fulfilled the eligibility criteria, representing 22 358 person-observations from five different countries. With the additional unpublished data from the 14 101 person-observations from the Finnish Public Sector study, the total number of person-observations was 36 459. The pooled estimates were derived from 2 to 5 studies, with the number of observations ranging from 260 to 26 348. Older age (pooled relative risk [RR] 0.95; 95% confidence interval [CI] 0.84–0.87), somatic comorbidity (RR = 0.80, 95% CI 0.77–0.83), psychiatric comorbidity (RR = 0.86, 95% CI 0.83–0.88) and more severe depression (RR = 0.96, 95% CI 0.94–0.98) were associated with a lower rate of return to work, and personality trait conscientiousness with higher (RR = 1.06, 95% CI 1.02–1.10) return to work. While older age and clinical factors predicted slower return, significant heterogeneity was observed between the studies. There is a dearth of observational studies on the predictors of RTW after depression. Future research should pay attention to quality aspects and particularly focus on the role of workplace and labor market factors as well as individual and clinical characteristics on RTW.